2013
DOI: 10.1016/s1836-9553(13)70143-7
|View full text |Cite
|
Sign up to set email alerts
|

Radial nerve mobilisation had bilateral sensory effects in people with thumb carpometacarpal osteoarthritis: a randomised trial

Abstract: Radial nerve gliding applied to the symptomatic hand induced hypoalgesic effects on the contralateral hand in people with CMC osteoarthritis, suggesting bilateral hypoalgesic effects of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…Clinicians should take into account the presence of central sensitization and widespread pressure pain hypersensitivity in this pain population by not limiting their intervention to the injured area. For instance, recent evidence showed that upper limb manual treatments were effective for improving pressure sensitivity over the injured area, even though they were not specifically directed to the first CMC joint [39][40][41][42][43][44]. Therefore, treatments applied to patients with thumb CMC OA should be targeted to address sensitization mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should take into account the presence of central sensitization and widespread pressure pain hypersensitivity in this pain population by not limiting their intervention to the injured area. For instance, recent evidence showed that upper limb manual treatments were effective for improving pressure sensitivity over the injured area, even though they were not specifically directed to the first CMC joint [39][40][41][42][43][44]. Therefore, treatments applied to patients with thumb CMC OA should be targeted to address sensitization mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The thumb CMC joint is frequently affected by osteoarthritis (OA), a degenerative condition that can result in deterioration of the joint surfaces1, 2 ) . Individuals with CMC joint OA have decreased pinch strength that impacts hand function and their ability to perform resistive pinch tasks such as clipping nails, turning keys, or opening food packages3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The tip and tripod pinch strength were unchanged as well. 9 Two trials studying the effect of radial nerve mobilization on patients with thumb CMC OA found it to have hypoalgesic effects on the same 10 and contralateral hand, 11 indicating bilateral hypoalgesic effects of the practice. In addition, tip pinch strength and tripod pinch strength both improved in the same hand.…”
Section: Resultsmentioning
confidence: 99%
“…20 Within balneotherapy, the use of sulphurous spa water alone was shown to be more effective than that of warm tap water exclusively in the reduction of pain in patients with hand OA. 21 Another Radial nerve mobilization 10,11 Arnica gel 30 Metacarpal osteotomy 45 Maitland's passive accessory mobilization 12 Topical analgesic + paraffin bath therapy 31 Carpometacarpal arthrodesis 45 Joint mobilization + neural mobilization + exercise 13 Intraarticular corticosteroid injections [32][33][34][35] Joint replacement 45 Custom-made splinting 17,18 Intraarticular hyaluronic acid injections 36 single-blind RCT showed that paraffin bath therapy in patients with bilateral hand OA was successful in reducing stiffness and pain at rest and during activities of daily living. As well, range of motion was enhanced in one hand, and muscle strength was better maintained as compared to the control group.…”
Section: Resultsmentioning
confidence: 99%